UNDERSTANDING ANTECEDENTS WHICH SHAPE TOURISTS’ WILLINGNESS TO VISIT FROM THE TPB VIEWPOINT - Keni, Keni; Wilson, Nicholas; Candraningrat, Ica Rika; Puspitowati, Ida (Jurnal Ilmiah Ekonomi Bisnis, 2024)
Theory of planned behavior (TPB) had been used repeatedly by various researchers to analyze human’s behavior. Utilizing this framework, this research attempts to fully investigate various variables which could affect tourists’ willingness to visit Bintan Island in Riau Island, Indonesia. Questionnaires were used to gather data from the qualified respondents who’ve visited Bintan Island at least once in the past 1 year. Next, a non-probability sampling in the form of purposive sampling was implemented in order to ensure that all respondents who filled in the questionnaires had satisfied the criteria. After distributing the questionnaires to the respondents for around 4 months, a total of 198 data had been successfully gathered from the respondents. However, after further assessment, 24 data need to be omitted since these data were filled in by respondents who failed to fulfill the respondents’ criteria set in this study, thus confirming that a total 174 data will be further assessed in this research using PLS-SEM method using SmartPLS 4 software. After analyzing these data, authors concluded that all three main variables within the TPB theory, namely attitude, perceived behavioral control and subjective norms, together with destination attachment, significantly and positively affect tourists’ willingness to visit Bintan Island.